Development of Project Based-Learning English Learning Materials for High School Students - Silvia, Silvia (Program Magister Teknologi Pendidikan Universitas Jambi, 2018)
This research aims to develop English language learning materials based on project based learning for class XI high school students at SMAS Adhyaksa 1 Jambi City. The teaching materials and practice assignments presented are designed for English subjects so that they are easy for students to understand and the context is adapted to students' daily lives. Through this approach, it is hoped that students will be able to increase their cognitive and psychomotor levels in English learning situations. Students are focused on how to observe and understand the material presented. The development model uses the ADDIE model (analysis, design, develop, implementation, and evaluation). The development procedures carried out follow the ADDIE design, these steps are: 1. Analysis; 2. Design; 3. Development; 4. Implementation; 5. Evaluation. The overall research results show that the learning material has a fairly good category. According to educational design experts, this learning material is effective, so it is suitable for use as English learning material. Meanwhile, subject matter experts gave a good assessment of the developed learning material. The learning materials developed by showing existing criteria and procedures are quite effective. During the field test, teachers and students gave a fairly good assessment of the development of this learning material.